2010
DOI: 10.1007/s11250-010-9614-2
|View full text |Cite
|
Sign up to set email alerts
|

Causes of calf mortality in peri-urban area of Nairobi, Kenya

Abstract: The study reported data from 507 post-mortem records in the Department of Pathology, Microbiology and Parasitology, Faculty of Veterinary Medicine, University of Nairobi, Kenya. The records were from carcasses obtained from the peri-urban area of Nairobi during a 20-year period between 1990 and 2009. Approximately 80% (393/507) of the calf carcasses had their diagnosis made through post-mortem examination, while the rest (114/507) were inconclusive. Just less than half (48.3%) of the calf carcasses presented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Mortality as a result of diarrhea was 63% (46.4, 79.4) and 17% (was related to respiratory problems). e major causes of calf mortality reported worldwide are diarrhea (calf scours) and respiratory diseases [4,18]. Previous studies in Ethiopia, which involved a longitudinal follow-up, also showed diarrhea as the first important disease of calves [6,7], and its prevalence appears to be management-related, especially when calves are housed in unhygienic conditions [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality as a result of diarrhea was 63% (46.4, 79.4) and 17% (was related to respiratory problems). e major causes of calf mortality reported worldwide are diarrhea (calf scours) and respiratory diseases [4,18]. Previous studies in Ethiopia, which involved a longitudinal follow-up, also showed diarrhea as the first important disease of calves [6,7], and its prevalence appears to be management-related, especially when calves are housed in unhygienic conditions [7].…”
Section: Discussionmentioning
confidence: 99%
“…Abortion is a condition where fetus is delivered live or dead before reaching survivable stage visualized by naked eye (Sarder et al, 2010). The success of any commercial dairy farms mainly depends on the survival rate of calf crop produced by the dairy farms, but most of the dairy farms are confronted with acute problems of calf morbidity & mortality (Wudu et al, 2008;Gitau et al, 2010). Abortions cause significant…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GI) and respiratory diseases are the leading causes of calf morbidity and mortality in Kenya and Elsewhere [ 1 - 3 ]. GI diseases in calves can be caused by protozoa such as Cryptosporidium , Coccidia , and Giardia; bacteria such as Escherichia coli ; and viruses such as rotavirus and coronavirus [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%